Performance analysis of multiuser MIMO system with adaptive modulation and imperfect CSI - Yin, Xin; Yu, Xiangbin; Liu, Yan; Tan, Wei; Chen, Xiaomin (2013 IET International Conference on Information and Communications Technologies : April 27-29, 2013, Beijing, China, 2013)
Based on imperfect channel state information (CSI), the performance analysis of multiuser multiple-input multiple-output (MIMO) system with rate adaptive modulation (AM) and antenna selection is presented. By means of approximate expression of bit error rate (BER) under imperfect CSI, the variable switching thresholds (ST) subject to a target BER constraint are derived. By the ST, a tightly approximate BER is derived to simplify the calculation of exact BER, which has more accuracy than the existing approximate BER to evaluate the impact of feedback delay on the system performance. The simulation results show that the multiuser MIMO with AM can provide better SE than the single user counterpart. Compared with the fixed ST, the variable ST is able to reduce the effect of feedback delay on BER. Additionally the system in the presence of imperfect CSI only has slight BER performance degradation for the normalized time delay less than 0.01.